(untitled) - Thomas, A. F. (Tokyo, 1936)
This book lays no claim to originalty. It is nothing more than an attempt to put succinctly into English what Japanes writers have written of the growth of commerce in Japan from early times.
Keywords: Nhật Bản,Japan; Thương mại,Lịch sử,Commerce,History